2016
DOI: 10.1371/journal.pone.0145074
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to the Uptake and Maintenance of Healthy Behaviours by People at Mid-Life: A Rapid Systematic Review

Abstract: BackgroundWith an ageing population, there is an increasing societal impact of ill health in later life. People who adopt healthy behaviours are more likely to age successfully. To engage people in health promotion initiatives in mid-life, a good understanding is needed of why people do not undertake healthy behaviours or engage in unhealthy ones.MethodsSearches were conducted to identify systematic reviews and qualitative or longitudinal cohort studies that reported mid-life barriers and facilitators to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
230
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(267 citation statements)
references
References 78 publications
23
230
0
7
Order By: Relevance
“…The sum score of social environmental barriers subgroups to PA (lack of support, lack of time, social influence, and social norms barriers) showed that the lack of time engaged in PA was the most important subgroup barriers for PA social environmental barriers among the study population. These findings were in agreement with previous studies [52,57,59]. However, in our study, the other social environmental subgroups barriers that also had a considerable impact on the women's PA included the lack of support from family and friends and a lack of social influence and norms.…”
Section: Physical Activity (Pa) Level and Its Perceived Barrierssupporting
confidence: 94%
See 1 more Smart Citation
“…The sum score of social environmental barriers subgroups to PA (lack of support, lack of time, social influence, and social norms barriers) showed that the lack of time engaged in PA was the most important subgroup barriers for PA social environmental barriers among the study population. These findings were in agreement with previous studies [52,57,59]. However, in our study, the other social environmental subgroups barriers that also had a considerable impact on the women's PA included the lack of support from family and friends and a lack of social influence and norms.…”
Section: Physical Activity (Pa) Level and Its Perceived Barrierssupporting
confidence: 94%
“…The sum score of the social environmental barriers subgroups to HE (lack of time, social influence, and lifestyle changes) showed that the lack of time to prepare and plan healthier meals (due to family commitments and social activities) was the most important social environmental barriers to HE among the study population. In previous studies, lack of time was one of the most frequently reported barriers in developed and developing countries [39,52,57,58]. In the current study, when the response categories very likely and somewhat likely were combined, the lack of time related to family and social commitment (reported by 39.5%) was more common than the lack of time due to job demands (34.1%) in the study population.…”
Section: Eating Habits and Perceived Barriers To Healthy Eatingmentioning
confidence: 44%
“…Other participants spoke about lack of social support being a barrier to PA, explaining they were less likely to engage in PA if they did not have a companion. Kelly et al (2016) included studies that identified social support as a facilitator (Hooker et al, 2011;Babakus and Thompson, 2012) and those that identified lack of social support as a barrier (Im et al, 2013). Whilst we had too few participants from different ethnic groups to comment on important effects, cultural and ethnic differences can help to explain why some people place more importance on social support, in terms of PA, than others.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Tier 3 referrals) and those who consume alcohol, in terms of the effects that they have on ERS adherence. Previous studies regarding barriers to PA have either not focused specifically on ERS 13 or have only recorded barriers for participants that have dropped out 14 , making comparisons to this study difficult. Further investigation into why a lack of motivation or childcare predict adherence is required, as the findings appear counterintuitive At present there is no available research regarding secondary care referrals as they have been excluded from most studies and recent systematic reviews 3 15 .…”
Section: Main Findings Of This Studymentioning
confidence: 99%